2005
DOI: 10.1016/j.agsy.2004.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Co-evolutionary scenarios of intensification and privatization of resource use in rural communities of south-western Niger

Abstract: Agricultural production in the semi-arid agro-ecosystems of the Sahel centres on cereal staple crops and pastoralism with increasing crop-livestock integration. Animals mobilize soil fertility through manure production, graze crop by-products, and transfer nutrients from distant pastures to cropped areas. Yet in these systems various interacting factors, i.e. climate variability, poor soil fertility, poverty, and institutional constraints limit the capacity of agriculture to keep pace with the growing needs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…Several other studies (e.g. Chikowo et al 2014;Gandah et al 2003;La Rovere et al 2005;Tittonell et al 2005a) have shown that soil fertility management and the use of production inputs are strongly related to the degree of access to resources that farmers have (e.g. carts, cattle manure, labour, mineral fertilizers and cash/credit).…”
Section: Discussionmentioning
confidence: 97%
“…Several other studies (e.g. Chikowo et al 2014;Gandah et al 2003;La Rovere et al 2005;Tittonell et al 2005a) have shown that soil fertility management and the use of production inputs are strongly related to the degree of access to resources that farmers have (e.g. carts, cattle manure, labour, mineral fertilizers and cash/credit).…”
Section: Discussionmentioning
confidence: 97%
“…Processes of intensification of livestock production by pastoralists are taking place across West Africa (Ramisch 1998;Buhl 1999;Demirag 2004;La Rovere et al 2005). Processes which involve crop-livestock interactions are generally studied within an evolutionary framework of mixed-farming systems, rather than pastoral systems (Powell et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These changes align perfectly with the dynamics already observed in other African countries and particularly in the West African sub-region (cf. Ayantunde et al 2000;Boutrais, 2000: 184;Moritz, 2003;Mortimore, 2005;Juul, 2005a;La Rovere et al 2005;Moritz et al 2009). …”
Section: Technological Change and Political Ecology 92 Of Developmenmentioning
confidence: 99%
“…Fulani pastoralists in northern Nigeria also rely upon various integrative practices to improve the productivity and the sustainability of their lands (Mortimore and Adams, 1998;Mortimore, 2003;. The integration of crops and livestock also allow Fulani herders in southwestern Niger to improve the productivity of their herds within a context of population growth and agricultural expansion (Ayantunde et al 2000;La Rovere et al 2005). Borana pastoralists in southern Ethiopia have shifted from pure pastoralism to agro-pastoralism in response to climate risks, rangeland degradation and population growth (Gemtessa et al 2007;Little et al 2010.).…”
Section: Agro-pastoral Integrationmentioning
confidence: 99%
See 1 more Smart Citation